Sarana Dan Prasarana Pada Madrasah Atau Sekolah Untuk Meningkatkan Kualitas Pembelajaran - Febby Eka Putri Saiful; M. Wildan Khadamul (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Educational facilities and infrastructure at schools or at madrasas are one of several important resources in the progress of an institution. Facilities and infrastructure are very important in education so that learning can run well and appropriately. In order for education in schools or madrasas to run effectively, complete and well-organized educational facilities can be utilized to the fullest extent possible to support a quality teaching and learning process. With well-maintained and well-maintained educational facilities and infrastructure, they will be able to function and be used as they should. This study uses a qualitative approach with data collection techniques through interviews, observation, documentation. This study aims to examine, identify and explain school facilities and infrastructure through several functions, namely planning facilities and infrastructure, procuring school facilities and infrastructure, maintaining school facilities and infrastructure, maintaining school facilities and infrastructure. The results of this study indicate that the facilities and infrastructure in schools have met the standards, the use of infrastructure facilities in the learning process must still be improved, as a continuous improvement in service quality to meet the realities and expectations of customers